DAMPAK VOLATILITAS HARGA MINYAK DI INDONESIA TERHADAP PENYESUAIAN KESEIMBANGAN FISKAL - Sujai, Mahpud (Jurnal Kajian Ekonomi dan Keuangan, 2011)
This paper is intended to analyze the effect of oil price changes on potential output and actual output in the state budget cycle and identifies the output gap which is the difference between potential output and actual output. The research methodology uses a quantitative approach to analyze problems that occur related to the impact of oil price changes to the state budget cycle. Data analysis was carried out through the approach cyclically adjusted fiscal balance with a simplified approach. This research identified that the potential output is likely to continue increasing in line with Indonesia's oil price trends which is continue to rise following the world oil price movements. In calculating the output gap using a linear trend and HP filter, the result is fuctuating depend on the percentage changes in both potential output and actual output. This paper concludes that Indonesian oil price (ICP) has a significant impact on changes in the state budget cycle. If oil prices rise, the output gap between potential output and actual output is greater, and vice versa. This will make the budget vulnerable to shock that occurs as an external infuence.